History of air warfare from World War I to the present day - Swanston, Malcolm; Swanston, Alexander (Amber Books, 2019)
A highly illustrated and accessible account of the development of air warfare, from the first skirmishes over the Western Front in World War I to today's hi-tech netcentric aerial battlespace. No single human invention has altered the nature of war more than the airplane. The History of Air Warfare charts these changes, from the earliest unpowered hot-air balloons through the many technological advances in aerodynamics, propulsion, radar, and the use of composites and engineered materials such as carbon fiber. Photographs and 120 complex computer-generated maps and graphics help explore every major battle fought in the world's skies, as well as to document the air element of campaigns such as Operation Barbarossa and Operation Desert Storm.